Investigating the adsorption of volatile organic compounds from kerosene using clinoptilolite (natural zeolite) modified by cationic surfactant cetyltrimethylammonium bromide - Motahareh Majidi Trojeni; Abdolraouf Samadi-Maybodi; Haniyeh Shafiei (MethodsX, 2025)
Volatile organic compounds (VOCs) from kerosene pose significant environmental and health risks, necessitating effective remediation strategies. In this work, the natural clinoptilolite zeolite was modified using cationic surfactant cetyltrimethylammonium bromide (CTAB) and it was applied as an adsorbent for adsorption of VOCs from kerosene. The adsorption efficacy (R%) was optimized using Experimental design. The parameters of contact time, pH and adsorbent dosage that can be potentially influence on the adsorption efficiency were considered in the optimization process. Results of the optimization process indicated that the highest of adsorption efficiency was obtained as follows: pH= 3.0, dose of adsorbent = 0.4 g and contact time 180 min. To find the behavior of adsorption, the isotherm models of Freundlich and Langmuir were studied. Also, thermodynamic analysis showed the process was spontaneous and endothermic. Results indicated the adsorption process follows a Langmuir isotherm model with a coefficient of determination (R2) of 0.9906. The adsorption of VOCs from kerosene by a cationic surfactant-modified zeolite was higher. This research underscores the potential of surfactant-modified clinoptilolite as a viable and efficient adsorbent for the remediation of VOC emissions from kerosene, paving the way for sustainable environmental practices. • Successfully modified natural clinoptilolite zeolite with cetyltrimethylammonium bromide (CTAB) to enhance VOC adsorption from kerosene. • Characterized the modified zeolite using Fourier transform infrared (FTIR) spectrophotometry and energy dispersive spectroscopy (EDX). • Achieved optimal adsorption efficiency with conditions of pH= 3.0, adsorbent dosage of 0.4 g and contact time of 180 min.